Influence of a nine-day alpine ski training programme on the postural stability of people with different levels of skills - Staniszewski Michał; Zybko Przemysław; Wiszomirska Ida (Sciendo, 2016)
Study aim: In alpine skiing, balance is one of the key elements that determine the effectiveness of the ride. Because of ski boots, the foot and ankle joint complex is excluded from the process of maintaining the stability of the body. The aim of the study was to determine to what extent a few days of skiing activities and the level of technical skills affect the skiers' level of postural stability.